Hubungan Antara Etos Kerja Karyawan Dengan Komitmen Pada Organisasi - Setiawan, Rizki Arif; , Achmad Dwityanto, S.Psi, M.Si (2017)
The human factor in the work world is very important especially its commitment on a company, because of the existence of a commitment of employees will then make a conducive of working conditions so that companies can run efficiently and effectively, so acquire to searched factors that affect organizational commitment. One of the factors that affect organizational commitment is the work ethic. The aim of this research is to know the relationship between work ethic with organizational commitment, so the authors propose the hypothesis "there is a positive relationship between work ethic with organizational commitment with ". The subject in this study is the employee of PT. Rosalia Express in Surakarta, which totaled approximately 153 employees, taken by technique sampling namely cluster random sampling, with the measurement intrument, namely: (1) the scale of the work ethic, and (2) the scale of the organization commitment. Data analysis in this study uses the product moment correlation. Based on the analysis results, so obtained correlation between work ethic with organizational commitment (r) amount of 0.562 with p = 0.000 where p < 0.01, this means there is a very significant positive relationships between the work ethic with the organizational commitment. That is, the higher the work ethics then the higher organizational commitment on employee, and conversely the lower work ethic then also lower organizational commitment on employee. The empirical mean of the work ethic variable is amount of 82.86 compared with hypothetic mean is amount of 77.5. So the empirical mean is greater than hypothetic mean, which means generally employees of PT. Rosalia Express, Surakarta has the medium of work ethic. Furthermore the empirical mean of organizational commitment variables is amount of 75.58 compared with hypothetic mean is amount of 60. So the empirical mean is greater than hypothetic mean, which means generally the employee of PT. Rosalia Express, Surakarta had a high organizational commitment. The role of organizational commitment towards work ethic (SE) amount of 31.6% means there is still 68.4% of other factors in addition to the work ethic that influence organizational commitment.